2016
DOI: 10.1007/s40744-016-0041-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Crossover Comparison of Injection Site Pain with 40 mg/0.4 or 0.8 mL Formulations of Adalimumab in Patients with Rheumatoid Arthritis

Abstract: IntroductionAdalimumab, an anti-tumor necrosis factor antibody, is currently available in a 40 mg/0.8 mL formulation. The objective of this analysis was to evaluate injection site-related pain, safety, and tolerability of a 40 mg/0.4 mL formulation of adalimumab that had fewer excipients, a smaller volume, and a delivery presentation with a smaller gauge needle, versus the current 40 mg/0.8 mL formulation in patients with rheumatoid arthritis (RA).MethodsTwo identically designed, phase 2, randomized, single-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 17 publications
(14 reference statements)
1
59
1
Order By: Relevance
“…Evidence to support the use of premedication with corticosteroids or antihistamines is limited, with patients still experiencing infusion reactions despite premedication and therefore should be considered on an individual basis. Injection site pain due to adalimumab can be reduced by using low volume formulations which are free from citrate buffers, with no change in efficacy …”
Section: Aims and Methodsmentioning
confidence: 99%
“…Evidence to support the use of premedication with corticosteroids or antihistamines is limited, with patients still experiencing infusion reactions despite premedication and therefore should be considered on an individual basis. Injection site pain due to adalimumab can be reduced by using low volume formulations which are free from citrate buffers, with no change in efficacy …”
Section: Aims and Methodsmentioning
confidence: 99%
“…Of note, any variations in ISP between originator and biosimilar biologics do not appear to reflect any differences in immunogenicity between these agents [23], with biosimilars reported to be effective and well tolerated in maintaining complete remission after the switch from the originator agent [24,25]. pH Bunke et al [26] suggested that the difference between the physiological pH of the tissue at Table 1 Factors contributing to subcutaneous injection-site pain Product-related factors Injection-related factors Patient-related factors • Formulation (ingredients, pH, buffers) [16,17,27,28,40] • Delivery volume [15,[32][33][34] • Needle gauge size [44] • Device type [49][50][51][52][53][54] • Injection speed [55][56][57][58] • Fluid viscosity [55] • Injection angle/technique [59,60] • Temperature of product [62,63] • Allergens [65,66] • Injection frequency [61] • Injection site [35] • Low body weight [68] • Injection anxiety/'needle phobia' [69,70] • Pain catastrophising [72] • Nocebo effect [73,74] • Female gender [67] • Fibromya...…”
Section: Product-related Factors Contributing To Sc Ispmentioning
confidence: 99%
“…Citrate‐free adalimumab was associated with a 54% mean reduction in pain compared to the standard formulation (Nash et al, ). Potential explanations for less pain with the citrate‐free formulation include use of a thinner needle (29 vs 27 G), 50% less volume for the same dose, and removal of the sodium citrate buffer (Abbvie, ; Nash et al, ). Citrate‐free adalimumab can be administered with an autoinjector and may serve patients who experience severe injection pain.…”
Section: Types Of Negative Injection Experiencesmentioning
confidence: 99%